Impact of naphthalene on soil fauna diversity: Consequences for ecosystem functioning and carbon cycling in grasslands - Chengyang Zhou; Gai Hang; Xiaonan Wang; Shining Zuo; Li Liu; Ding Huang (Ecological Indicators, 2024)
Soil fauna, key indicators of grassland ecosystem health, face significant threats from the vast amounts of chemical pollutants released by human activities. These organisms are crucial for fundamental processes such as litter decomposition and carbon cycling. However, the response of soil animal communities and their functional dynamics to environmental chemical stress remains poorly understood. To investigate this, we conducted a naphthalene addition and litterbag experiment in the Bashang Grassland, located on the southern Inner Mongolia Plateau, to analyze its effects on soil fauna and litter decomposition. The investigated soil fauna groups included Arachnida (Arachnids), Insecta (Insects), Collembola (Springtails), Enoplea (enopleans), and Chromadorea (chromadoreans). The litter composition included Leymus chinensis, Stipa krylovii, Artemisia, Saussurea amara, and Artemisia giraldii. The findings indicated that a high diversity of soil fauna enhanced the decomposition of litter and the release of organic carbon from the litter. While the addition of naphthalene decreased both the abundance of soil fauna and the rate of litter decomposition, it specifically increased the relative proportion of Collembola (Springtails). Microfauna and mesofauna (0.1–2.0 mm) contributed more to the loss of litter mass and the release of organic carbon from the litter than macrofauna (2.0–4.0 mm). The effects of diverse soil fauna on litter decomposition and soil organic carbon accumulation were diminished by naphthalene exposure. This study further reveals the relationship between composite soil fauna diversity, litter decomposition, and soil organic carbon under chemical stress, highlighting the threat of environmental pollution to ecosystem health. It also enriches our understanding of the complexity of grassland ecosystems, especially in response mechanisms under chemical pollution stress.